CASE REPORTSuccessful repeated thrombolysis in a patient with HeartWare thrombosis – the importance of Doppler flow pattern - Paluszkiewicz, Lech; Morshuis, Michiel; Hakim-Meibodi, Kavous; Ensminger, Stephan; Gummert, Jan (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2014)
Here we present a patient after implantation of a left ventricular assist device (HeartWare) for destination therapy complicated by recurrent thrombosis of the device. At 14 months after implantation, the patient presented with a pump thrombosis after an INR incompliance period. A surgical pump exchange was performed and the patient recovered uneventfully. Five months later a pump thrombosis occurred again, and the patient refused surgery. Systemic thrombolysis was carried out this time. Three and 6 months later the same clinical picture was presented again, and repeat thrombolysis was performed successfully. The patient was discharged and has remained stable since, without any symptoms of thrombosis of the device.